THE SEARCH FOR NATIONAL IDENTITY IN AZERBAIJAN DURING THE LATE 19th CENTURY - Sahbazov, Tahir S. (History, Archeology and Ethnography of the Caucasus, 2025)
Contemporary scholarship distinguishes various forms of identity – ethnic, national, religious, and others. Among these, the issue of “national identity” has attracted the widest discussion, since both the nation and nationalism are products of modern era in which national states are born and formed. For this reason, the history of national identity search in Azerbaijan and the formation of the Azerbaijani nation are of great relevance. Historical-comparative analyses conducted based on archival, source and literary materials reveal that until the 1870s, Azerbaijanis did not have a clear idea about the nation they belonged, the language they spoke, and the religion they had been carriers for centuries. The founding in 1875 of Hasan Bey Zardabi’s newspaper Ekinchi – published under considerable hardship – together with later outlets such as Ziya, Kashkul, and Kaspi, introduced Enlightenment thought and stimulated the search for national identity. Led by a small group of Russian– and European-educated democratic intellectuals, this movement advocated the use of the native language and alphabet, the development of national education, and the establishment of a domestic press, thereby igniting an ethno-cultural revival in Azerbaijan. By the end of the nineteenth century, through the efforts of intellectuals such as M.Shahtakhtli, A.b. Huseynzadeh, A.b.Aghaoglu, M.A.Rasulzadeh, A.b.Topchubashi and others, this movement had evolved into a mature national ideology with clearly articulated political goals and objectives. Finally, first democratic republic established in the Turkic-Muslim East against the backdrop of political, ideological, and national upheavals that began in the Russian Empire at early twentieth century – the Azerbaijan People’s Republic – can be considered the logical conclusion of the national identity search that began in the second half of the nineteenth century.
Keywords: primordialism; modernism; search for national identity; Yusif Akchura; Ekinchi